The voices of nihilism. The age of civilisational pathologies and agenesis subjectivity - Romero Martín, Francisco (Anales del Seminario de Historia de la Filosofía, 2024)
In this paper we will try to present nihilism as an ontological event whose mode of being would coincide with that of a pathogenic agent. In this way, and as pathogenic, this ontological crisis would be the cause of the global malaise that plagues the West. For this reason, we will focus on the symptomatological effects of its action, as well as on whether we can hope for a remedy to combat it. All this will be approached from the point of view of the main theses of the philosopher Luis Sáez Rueda.
Keywords: blind forces; event; nihilism; pathogenic agent; pathologies of civilization; schizophrenia